Making Life : How we reproduce and grow - Richard Walker (Grolier Educational, 1998)
While you are reading this, it could be happening in Bangalore, India, or Toronto, Canada. Or, perhaps, in Riyadh, Saudi Arabia, or Osaka, Japan...etc...